Treatment of IgG4-related disease-associated hypertrophic pachymeningitis with intrathecal rituximab: a case report - Balaban, Denis T.; Hutto, Spencer K.; Panzarini, Bruno P.; O'Shea, Aileen; Varma, Aditi; Jones, Pamela S.; Chwalisz, Bart K.; Stone, John H.; Venna, Nagagopal (Frontiers in Neurology, 2023)
IgG4-related disease-associated hypertrophic pachymeningitis (IgG4RD-HP) is a fibroinflammatory autoimmune disorder in which diagnosis is difficult without biopsy. Guidance on management of disease refractory to glucocorticoids and intravenous rituximab is limited. We present the case of a 68-year-old woman with IgG4RD-HP who developed sensorineural hearing loss with associated bulky basilar pachymeningeal enhancement. Her cerebrospinal fluid was inflammatory and had an elevated IgG4 concentration, strongly suggestive of IgG4RD-HP. Biopsy of involved meninges was not possible due to surgical risk. Over years she developed bilateral optic neuropathies and hydrocephalus, requiring intravenous rituximab and ventriculoperitoneal shunt. Her disease was refractory to glucocorticoids. Despite maintenance intravenous rituximab, she developed slowly progressive symptoms of intracranial hypertension and hydrocephalus with persistently inflammatory spinal fluid. Switching to intrathecal rituximab therapy led to dramatic improvement in gait and headache and reduced pachymeningeal bulk and metabolic activity. In patients with IgG4RD-HP refractory to glucocorticoids and intravenous rituximab, intrathecal rituximab may be an efficacious therapy.